Spray fabrication of superhydrophobic coating on aluminum alloy for corrosion mitigation. (March 2021) - Gong, Ao; Zheng, Yong; Yang, Zhengkai; Guo, Xiaoge; Gao, Yan; Li, Xiaoyu
Abstract: A novel superhydrophobic coating was fabricated by spraying with F-SiO2 nanoparticles, epoxy resin adhesive, fluorosilicone varnishes and white fluorinated polyurethane coatings. The wettability, surface roughness, surface morphology and surface chemical group of superhydrophobic coating were characterized. Mechanical stability, corrosion resistance and self-cleaning ability of superhydrophobic coating were examined. Results showed that superhydrophobic coating exhibited excellent water-repellency. The contact angle of superhydrophobic coating was 161.35° and the sliding angle was only 2.0°. The contact angles of superhydrophobic coatings after 20 continuous abrasion cycles, 1.5 h water dripping or 20 tape peeling cycles were all above 150°. Superhydrophobic coating had a significant enhancement in corrosion resistance. The corrosion potential and corrosion current density of coating after 20 d neutral salt spray accelerated corrosion test were -0.54 V and 5.26 x 10 −8 A cm -2, respectively. Sand adhered to superhydrophobic coating could be easily washed away, which revealed superhydrophobic coating exhibited excellent self-cleaning ability.